KESALAHAN SISWA DALAM MENYELESAIKAN SOAL SISTEM PERSAMAAN LINIER DUA VARIABEL BERDASARKAN KRITERIA WATSON DITINJAU DARI KEMAMPUAN MATEMATIKA DAN GENDER - Dewi, Miya Ayu Kumala; Trapsilasiwi, Dinawati; Yudianto, Erfan (Department of Mathematics Education , University of Jember, 2019)
The purpose of the research are to describe the types of students’ errors based on Watson's criteria assessed from their mathematical ability and gender, and examine the causes of students’ errors. This type of research is descriptive with a qualitative approach. Data collection methods used are observation and interviews. The subjects of the study were 6 students consisting of 3 male students and 3 female students of class VIIIB of SMP 4 Jember which each students represented a high, medium, and low level of mathematics ability. Based on the results obtained, many students experience errors when working on the Two Variable Linear Equation System problem, both for male and female students at the level of high, medium, and low mathematical abilities. Each type of error has a cause of error. Keywords: errors, gender, mathematical abilities, Watson's criteria, Two-Variable Linear Equation System